Empty pelvis syndrome: a systematic review of reconstruction techniques and their associated complications. (25th October 2021) - Johnson, Yanika L.; West, Malcolm A.; Gould, Laura E.; Drami, Ioanna; Behrenbruch, Corina; Burns, Elaine M.; Mirnezami, Alexander H.; Jenkins, John T.
Abstract: Aim: Empty pelvis syndrome is a major contributor to morbidity following pelvic exenteration. Several techniques for filling the pelvis have been proposed; however, there is no consensus on the best approach. We evaluated and compared the complications associated with each reconstruction technique with the aim of determining which is associated with the lowest incidence of complications related to the empty pelvis. Method: The systematic review protocol was prospectively registered with PROSPERO (CRD42021239307). PRISMA‐P guidelines were used to present the literature. PubMed and MEDLINE were systematically searched up to 1 February 2021. A dataset containing predetermined primary and secondary outcomes was extracted. Results: Eighteen studies fulfilled our criteria; these included 375 patients with mainly rectal and gynaecological cancer. Only three studies had a follow‐up greater than 2 years. Six surgical interventions were identified. Mesh reconstruction and breast prosthesis were associated with low rates of small bowel obstruction (SBO), entero‐cutaneous fistulas and perineal hernia. Findings for myocutaneous flaps were similar; however, they were associated with high rates of perineal wound complications. Omentoplasty was found to have a high perineal wound infection rate (40%). Obstetric balloons were found to have the highest rates of perineal wound dehiscence and SBO. Silicone expanders effectively kept small bowel out of the pelvis, although rates of pelvic collections remained high (20%). Conclusion: The morbidity associated with an empty pelvis remains considerable. Given the low quality of the evidence with small patient numbers, strong conclusions in favour of a certain technique and comparison of these interventions remains challenging.